Management of Educational Institutions through Information Systems for Enhanced Efficiency and Decision-Making - Sunarjo, Richard Andre; Chakim, Mochamad Heru Riza; Maulana, Sabda; Fitriani, Gaby (International Transactions on Education Technology (ITEE), 2024)
This paper explores the application of information systems in the management of educational institutions, aiming to enhance operational efficiency and support informed decision-making processes. Educational institutions face growing demands for streamlined administration and resource optimization, which form the background of this study. The objective is to assess the effectiveness of implementing information systems tailored to manage complex educational processes and institutional needs. A mixed-method approach was employed, combining quantitative analysis of system usage data and qualitative feedback from administrators and educators within various institutions. This method allowed for a comprehensive understanding of the impacts and challenges associated with integrating these technologies. Results reveal that institutions using information systems report significant improvements in administrative efficiency, resource management, and data-driven decision-making capabilities, as well as enhanced stakeholder satisfaction. Furthermore, the findings suggest that well-designed information systems reduce redundant administrative tasks, enabling staff to allocate more time toward core educational activities. In conclusion, the adoption of tailored information systems for educational institutions not only enhances management efficiency but also supports a culture of informed decision-making, paving the way for more responsive and adaptive educational environments. These insights underscore the value of integrating technology into educational administration, offering a strategic path toward more effective institutional management.